Coexisting driver mutations in MPN: clinical and molecular characteristics of a series of 11 patients. Issue 10 (26th November 2018) - De Roeck, L.; Michaux, L.; Debackere, K.; Lierman, E.; Vandenberghe, P.; Devos, T.
ABSTRACT: Objectives: CML, PV, ET and PMF are so called classical MPN with distinct clinical phenotypes. The discovery of the BCR-ABL1 translocation and mutations in driver genes JAK2, MPL and CALR has provided novel insights in their pathogenesis. While these mutations are thought to be mutually exclusive, rare cases of MPN with coexisting driver mutations have been reported. However, little is known about the clinical, biological and molecular characteristics of these patients and the interaction of the neoplastic clones. Methods: We retrospectively studied 11 MPN patients with coexisting driver mutations ( JAK2 V617F +  BCR-ABL1 : n  = 8; CALR type 2 +  BCR-ABL1 : n  = 1 ; JAK2 V617F +  MPL W515: n  = 1 ; JAK2 V617F +  CALR type 1: n  = 1). To assess possible associated molecular aberrations, we analysed DNA of six patients using NGS. Results: In four CML patients, decreasing BCR-ABL1 transcript levels with increasing JAK2 V617F allele burden under TKI were observed. This strongly suggests that the coexistence of driver mutations originates from two different clones growing independently. Additional somatic mutations were detected in 5 out of 6 (83%) patients affecting 4 different genes, confirming the heterogeneity of this study cohort. Suboptimal response to TKI was observed with a higher frequency (4/8 patients) than reported in conventional series of CML and the overall tolerance of treatment with hydroxyurea and/or imatinib in our series was poor. Conclusion: Given the emergence of NGS in clinical practice, more similar cases will be identified in the coming years. The optimal treatment strategy for this rare group of patients is uncertain and toxicity of combination treatment may have to be considered.